Daily Patterns of Emotional Functioning on Drinking and Nondrinking Days. (18th November 2020) - De Leon, Ardhys N.; Dvorak, Robert D.; Kramer, Matthew P.; Peterson, Roselyn; Pinto, Daniel A.; Leary, Angelina V.; Magri, Tatiana D.
Abstract : Background: Alcohol misuse continues to be a significant public health problem. Understanding the factors that may contribute to the harmful progression in drinking is an important aspect of public health. Previous research has shown that affect regulation is associated with problematic alcohol use. Additionally, emotion instability has been found as a predictor of alcohol‐related problems and may be linked to reinforcement mechanisms. Methods: The current study examined positive mood, negative mood, and mood instability in real time across drinking and nondrinking days utilizing ecological momentary assessment (EMA). Current drinkers ( n  = 74) were recruited for a 21‐day EMA study. Participants completed up to 10 random assessments of positive mood, negative mood, and alcohol use per day. Mood instability was assessed as the squared difference in current mood from mood in the previous assessment. Data were analyzed using piecewise multilevel regression to examine mood trajectories across drinking and nondrinking days. Results: Positive emotion across the day was higher on drinking days than nondrinking days and continued to increase after drinking initiation. In contrast, negative emotion across the day was lower on drinking days than nondrinking days and continued to decrease after drinking initiation. Emotional functioning was stable across the day on nondrinking days. However, on drinking days there was a steady increase in emotional instability leading up to drinking initiation, followed by a rapid stabilization after initiation. Conclusions: This study highlights the potentially reinforcing impact of alcohol via emotional stability. Overall, these findings highlight the importance of mood dynamics when examining the reinforcing effects of alcohol consumption. Abstract : This study examined indices of mood across drinking and non‐drinking days. Relative to nondrinkingdays, emotional functioning became increasingly unstable as individuals approached the time they began drinking. This was followed by a precipitous stabilization of mood, shortly afterdrinking began. Within ~90 minutes of initiating drinking, emotional functioning on drinking days had stabilized to levels similar to non‐drinking days. This suggests a negative reinforcementpattern whereby alcohol stabilizes emotional functioning, rather than simply decreases negative or increases positive emotion.